If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-2(6)=2
We simplify the equation to the form, which is simple to understand
x-2(6)=2
Reorder the terms in parentheses
x+(-12)=2
Remove unnecessary parentheses
+x-12=+2
We move all terms containing x to the left and all other terms to the right.
+1x=+2+12
We simplify left and right side of the equation.
+1x=+14
We divide both sides of the equation by 1 to get x.
x=14
| 3s^2=2s^2+1 | | 5x+4=-x-20 | | -10x-4x+13x=0-7 | | 5x-7(x-4)=51 | | 14x=(5x+14) | | y=xk | | .3.7(-83x-3)=3.7(7x-30) | | 3x+61=6x-11 | | 245-2x=43x+15 | | 5x-x=14*5 | | 6.7=-3.2+x | | 159-4x=23x+15 | | a=bc+d | | 96=5x^2-x^2 | | 41-7x=90 | | 1-5x-36x^2=0 | | 4x+1y=6 | | 3u^2-27= | | 2/1= | | 16-10w=-74 | | x-(x^2)=1 | | 5x+2x+x=8x^3 | | 5x+2x+x=8x | | 1/1= | | 64x=16x^3 | | 5x+2x+x=8 | | u^2+8u+16= | | 486=27r | | 1/-2= | | 17=1p-3-3p | | 3x-3y=15 | | a/4+3=-3 |